Phenolic acid profiles of common food and estimated natural intake with different structures and forms in five regions of China. (15th August 2020) - Song, Huaxin; Zhang, Liuquan; Wu, Lipeng; Huang, Weisu; Wang, Mengmeng; Zhang, Liangxiao; Shao, Yafang; Wang, Meng; Zhang, Fang; Zhao, Ziyan; Mei, Xiaohong; Li, Tao; et al.
Highlights: Phenolic acids intake of Chinese residents have been assessed for the first time. 16 phenolic acids in 116 foods from five regions of China were determined. Free, esterified and bound phenolic acids were determined. The dietary intake of food refers to the data of 2009–2013 and 2002. Abstract: Phenolic acids have been reported to have many biological activities, but daily intake information is scarce. In this study, the phenolic acid contents of 116 commonly consumed food in five regions of China (Beijing, Hangzhou, Wuhan, Chongqing and Guangzhou) were analyzed by high performance liquid chromatography-mass spectrometry (HPLC-MS) and dietary intakes estimated. Tea had the highest total phenolic acids (TPA) content in all regions investigated. Phenolic acids were in esterified and bound forms, and hydroxycinnamic acids accounted for more than half of TPA content, except in tea and legumes. Average TPA intake was 193.50 mg/ day at the national level but ranged from 157.09 to 263.01 mg/ day among the regions. Rice, tea, and fruits were the main contributors to dietary intakes of TPA. Also, TPA intake in the period 2009–2013 increased 31.65 mg/ day compared with 2002, largely due to increased intakes of fruits, vegetables, and legumes.